A Communication Approach to El Salvador's EDUCO Education Reform Efforts - Basaninyenzi, Uwimana (World Bank, Washington, DC, 2017)
A well-designed communication plan proved to be critical in implementing successful education reform efforts in El Salvador (World Bank 1998). El Salvador's experience with the Education with Community Participation Program (EDUCO) demonstrated that special emphasis on communication strategies can build consensus, inform communities, and improve public support for complex reforms. During the 1990s, efforts to reform El Salvador's failing schools mobilized a number of actors that included rural communities, education stakeholders, and government officials. The results revealed acute shortages in basic resources that were largely tied to conditions caused during El Salvador's civil war (1980-92). At that time, many public schools in rural areas were forced to close because of security concerns and lack of public resources. The teachers that were contracted were not paid consistently and often unable to teach in the impoverished conditions. This project was financed by the World Bank along with other multilateral organizations from 1995 to 2007 (World Bank 2007). In this program, local school-based parent associations (community education associations [ACEs]), given appropriate training, were granted control over the administration of schools. This proved to be a challenge as low literacy rates were common among members of the ACEs. A lot of parents especially mothers were not able to read and write. Therefore, a training program was developed to improve literacy among parents and increase the participation among women. Financial management was also a part of these capacity-building efforts, where parents were trained to manage the funds of the associations.